Neurospora crassa clock-controlled genes are regulated at the level of transcription. - Loros, J J (1991)
Although an extensive number of biological processes are under the daily control of the circadian biological clock, little is known about how the clock maintains its regulatory networks within a cell. An important aspect of this temporal control is the daily control of gene expression. Previously we identified two morning-specific genes that are regulated by the clock through daily control of gene expression (J. Loros, S. Denome, and J.C. Dunlap, Science 243:385-388, 1989). We have now introduced a method for transcriptional analysis in Neurospora crassa and used this nuclear run-on procedure to show that regulation of mRNA abundance for these two morning-specific genes occurs at the level of transcription. This transcriptional regulation by the circadian clock provides a basis for isolating circadian rhythm mutants.